Impact resistance of hybrid glass fiber reinforced epoxy/nanoclay composite. (February 2017) - Rafiq, Ahmad; Merah, Nesar; Boukhili, Rachid; Al-Qadhi, Muneer
Abstract: The effect of nanoclay addition in Glass Fiber Reinforced Epoxy (GFRE) composites on impact response was studied. The epoxy nanocomposite matrix with 1.5 and 3.0 wt% loading of I.30E nanoclay was produced by high shear mixing. Hybrid GFRE nanoclay composite plates were manufactured by hand layup and hot pressing techniques using electrical grade-corrosion resistant (E-CR) glass fiber mats. The laminates were then subjected to low-velocity impact with energies between 10 and 50 J. Addition of nanoclay was found to improve peak load and stiffness of GFRE. Nanoclay loading of 1.5 wt% resulted in optimum properties, with 23% improvement in peak load and 11% increase in stiffness. A significant reduction in physical damage was also observed for hybrid nanocomposite samples as compared to GFRE. This was mainly attributed to transition in damage mechanism due to nanoclay addition. Clay agglomeration in samples with 3.0 wt% loading contributed towards limiting the improvement in impact resistance.